2003
DOI: 10.1046/j.1460-9568.2003.02876.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity‐dependent increase of net matrix metalloproteinase activity is associated with MMP‐9 neurotoxicity after kainate

Abstract: Matrix metalloproteinases (MMPs) and the tissue inhibitors of MMPs (TIMPs) are emerging as important modulators of brain physiopathology. Dramatic changes in the expression of MMPs and TIMPs occur during excitotoxic/neuroinflammatory processes. However, only the measurement of net protease activity is relevant physiologically, and the functional consequences of MMP/TIMP ratio modifications in the brain remain elusive. In order to assess MMP activity and effects in brain tissue, we combined in vivo and organoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
143
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 41 publications
10
143
0
2
Order By: Relevance
“…This is consistent with many other reports regarding proinflammatory and neurotoxic properties of fAβ [11,30,44]. Furthermore, increased expression of MMP-9 by nfAβ , as observed herein, may amplify microglial toxicity through its direct neurotoxic effect and ability to facilitate maturation of pro-IL-1β [45,46].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with many other reports regarding proinflammatory and neurotoxic properties of fAβ [11,30,44]. Furthermore, increased expression of MMP-9 by nfAβ , as observed herein, may amplify microglial toxicity through its direct neurotoxic effect and ability to facilitate maturation of pro-IL-1β [45,46].…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have linked MMPs to various pathologic conditions in the central nervous system, including ischemia, multiple sclerosis, Parkinson's disease, malignant glioma, Alzheimer's disease, and epilepsy. Interestingly, some evidence suggests that, in addition to its known extracellular role in macromolecule degradation, MMP may mediate apoptotic and/or necrotic cell death (Jourquin et al, 2003;Kim et al, 2009) and synaptic plasticity (Tian et al, 2007;Wilczynski et al, 2008;Takács et al, 2010). The gelatinases MMP-2 and MMP-9 are initially expressed as inactive proenzymes that are cleaved to their active forms after they are released from cells (Van den Steen et al, 2002), allowing these proteases to regulate the levels of extracellular substrates.…”
Section: Discussionmentioning
confidence: 99%
“…After seizure, MMP-9 mRNA is transported to dendrites and synapses in the hippocampal DG of kainic acid-treated rats . Jourquin et al (2003) used organotypic cultures to demonstrate increased release and activity of MMP-9 after stimulation with neurotoxic kainate and reduced neuronal cell death following MMP-9 inhibition. Although MMP-9 is expressed in response to neural activity in some models of epileptogenesis (Wilczynski et al, 2008;Kim et al, 2009;Takács et al, 2010), the pathophysiologic and etiologic roles of this metalloproteinase, including potential molecular targets, during kindling seizure development have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The most obvious example is excitotoxicity, which occurs if glutamate receptor activation becomes excessive or prolonged, leading to the point where the target neurons become damaged and eventually die, for example, in the CA1 and CA3 hippocampal subfields after the kainate 25,26 and indeed using kainate treatment of the organotypic hippocampal cultures Jourquin et al 15 showed that MMP-9 is directly involved in the excitotoxic neuronal loss. Furthermore, overexpression of TIMP-1 in such cultures showed neuroprotective effect after excessive glutamate stimulation.…”
Section: Mmp-9 In Neuronal Deathmentioning
confidence: 99%
“…[6][7][8][9] MMP-9 is expressed ubiquitously, albeit at low levels, in various mammalian organs and tissues, including the adult brain 10,11 where it is produced mainly by neurons, and, to some extent, by glia. [12][13][14][15] Recently, we studied a subcellular localization of MMP-9 in the rat hippocampus, using highresolution morphological as well as biochemical approaches. 16 At the ultrastructural level, MMP-9 was found to be present in a subset of dendritic spines bearing asymmetric (e.g.…”
mentioning
confidence: 99%